Effect of Financial Literacy and Financial Inclusion on Financial Behavior Moderated by Self-Control - Salwa Nuraeni; Ningsih, Winda; Fitri Syakinah (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2026)
This study aims to determine the effect of financial literacy and financial inclusion on the financial behavior of Gen Z students in Garut Regency, using self-control as a moderating variable. The research questions asked are whether financial literacy, financial inclusion, and self-control influence financial behavior, and whether self- control can moderate the relationship between financial literacy and financial inclusion. The research was conducted because there is still limited research that focuses on Gen Z students in Garut Regency. The research method used is a quantitative approach, with questionnaires distributed to 362 students in Garut Regency selected through purposive sampling. The data collected is primary data. The data analysis was carried out using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results of the study indicate that financial literacy, financial inclusion, and self-control have a positive and significant effect on financial behavior. Self-control as a moderating variable shows a significant influence in strengthening the relationship between financial literacy and financial behavior. And self-control can moderate the effect of financial inclusion on financial behavior, but weaken it. These findings indicate that students' understanding of financial literacy, financial inclusion, and self-control abilities are very important factors in shaping positive financial behavior.